(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Women play a significant role in driving the econ omy of the world. Companies that sell to both men and women have always had larger market share. In India the number of female Two-wheeler users is rising very rapidly and the overall de mographic profile of the Two-wheeler users has undergone a drastic change. The Two-wheeler is considered to be the most convenient and eco nomical mode of transportation. The COVID crisis has further helped in giving a boost to the sales of Two-wheeler as people would now reduce their dependency on the public means of trans portation. This has created a huge opportunity for the Two-wheeler companies. In India Two-wheeler manufacturing companies indulge in aggressive marketing techniques and launch new models with latest technology to impress the customer. Internet now is considered as a vital medium of communication with the customers as more and more people; especially the young are hooked to the internet. The study tries to analyse the influ ence of internet on the users of the Two-wheeler and the impact of celebrity endorsement on the buying decisions. The research undertaken makes an attempt to understand the preferences of male and female Two-wheeler users and the important factors that motivate buyers to choose a particular brand of Two-wheeler. The study explains certain factors, which the consumers consider more significant as compared to other factors. It hopes to shed light on the role of family members and friends on the buying decisions. An attempt is made to analyse the changing consumer behaviour with reference to buying a Two-wheeler. The research aims to find the most preferred Two-wheeler brand in Palghar district. The study undertaken will provide new insights into the aspects that are considered most significant by Two-wheeler users irrespective of the gender thereby helping managers making better decisions that will lead to attracting more customers. The implementation of the suggestion proposed at the end of the study will hopefully result in higher levels of customer satisfaction. The research is significant as it hopes to lay a foundation for further studies on similar lines which can be replicated in other parts of the country. It will also provide new insights and help look at things from the perspective of the buyer